Increasing The Quality and Quantity of Marine Processed Production in Fisherman Villages - Febby Rahmatullah Masruchin; Ratnaningsih Sri Yustini; Naufal Abdillah (IPTEK Journal of Proceedings Series, 2023)
The processed sea is one of the livelihood commodities in the fishing village of Surabaya. The production process includes cleaning, drying, cooking, and packaging activities. One of the problems faced is in the drying process. Dry on the highway makes the product unhygienic. Horizontal drying areas have a limited area for drying. The solution given to this problem is a multifunctional vertical drying area. Vertical drying racks can increase the quantity of drying up to 5 times. Product quality can also be improved because there is no drying on the edge of the highway which causes the product to be less hygienic. The multifunction of the drying area is obtained from 3 main functions: a drying place, a storage area, and an oven. The use of metal material aims to make the drying place have a longer life than bamboo. The use of metal angled holes is intended so that the distance between rack levels can be adjusted to the needs and can be added or reduced. The increase in the quantity and quality of production in the drying process is expected to increase the profits of the business of processed marine products in the Surabaya fishing village.